From Lignocellulosic Residues to Protein Sources: Insights into Biomass Pre-Treatments and Conversion - dos Anjos, Isabela Vera; Coelho, Natacha; Duarte, Hugo; Proença, Diogo Neves; Duarte, Maria F.; Barros, Raul; Raposo, Sara; Gonçalves, Sandra; Romano, Anabela; Medronho, Bruno (Polymers, 2025)
With the global population steadily rising, the demand for sustainable protein sources has become increasingly urgent. Traditional animal- and plant-based proteins face challenges related to scalability, resource efficiency, and environmental impact. In this context, single-cell protein has emerged as a promising alternative. Derived from microorganisms such as algae, bacteria, fungi, and yeast, single-cell protein offers a high nutritional profile- including all essential amino acids and vitamins—while enabling rapid production, minimal land and water requirements, and no generation of greenhouse gas emissions. A particularly compelling advantage of single-cell protein is its ability to be produced from agro-industrial waste, converting low-cost residues into valuable nutritional resources and contributing to environmental sustainability. Among these waste streams, lignocellulosic biomass from agricultural and forestry residues stands out as a renewable, biodegradable, and abundant feedstock. This review explores the potential of lignocellulosic waste as a substrate for single-cell protein production, emphasizing both its environmental advantages and nutritional value. It highlights the single-cell protein role as a sustainable and scalable alternative to conventional protein sources. The review also identifies key scientific, economic, and regulatory challenges, and recognizes the importance of targeted investments, particularly in policy development, public awareness, and technological innovation, to enable the broader adoption and acceptance of single-cell protein -based products.